Sendangagung Bangkit: Bangun Kemandirian Pangan dan Ekonomi Desa Di Masa Pandemi Covid-19 - Alifian Gigih Pangestu; Irvan Ardi Saputro; Rizal Umami; Imroatus Sholikah; Ayu Rizki Rosiana Putri; Siti Maryamah; Yuyun Mardiana; Niswatul Khoiriyah; Pipit Novita Indriani; Naila Khoirun Nafisah; Dias Indrasti (Jurnal Pusat Inovasi Masyarakat (PIM), 2021)
The Covid-19 outbreak caused by the Corona virus or Severe Acute Respiratory Syndrome Coronavirus-2 (SARS-CoV-2) in early 2020 has claimed a lot of casualties and losses to the community, so people have to apply physical distancing. KRPL (Sustainable Food House Area) is one of the efforts that can be made to meet the food needs of the community by utilizing the house yard for farming. The program through the application of the KRPL system is expected to be a solution to fulfill food needs independently of the community as well as support the readiness of implementing physical distancing. This activity was carried out from July 6 to August 18, 2020 in Mediumagung Village, Pamotan District, Rembang Regency with the aim of disseminating Covid-19 education to the public and providing food security solutions in the midst of a pandemic by optimizing household yards as household food gardens. by continuing to implement the Covid-19 protocol. Group have carried out education related to the KRPL program and its implementation in the form of making simple aquaponics and verticulture installations as an alternative to food security during the Covid-19 pandemic. KRPL program with a simple aquaponics system using a bucket for catfish storage and a plastic cup container as a planting medium. Verticulture system using used bottles as a container for planting media. Keywords: food security, physical distancing, Sendangagung